2019
DOI: 10.1186/s40942-019-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

The retinal foveal avascular zone as a systemic biomarker to evaluate inflammatory bowel disease control

Abstract: Background Inflammatory bowel disease (IBD) is a systemic inflammatory disease and is classified as Crohn’s disease (CD) or ulcerative colitis (UC) depending on the extent of gastrointestinal tract involvement. IBD can be associated with extraintestinal findings, such as fever, weight loss, arthralgia, and mucocutaneous lesions, as well as hepatic, renal and ophthalmological involvement. Clinical parameters and colonoscopy are used to establish the criteria for controlled or non-controlled disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
(21 reference statements)
0
14
1
Order By: Relevance
“…If this is just a local finding or similar changes could be found in other organs remains an unsolved question. Other studies have suggested VD in central retina as a possible vascular biomarker and examined its relationship with systemic conditions: diabetes, 23 chronic kidney disease, 24 inflammatory bowel disease, 25 amyloidosis 26 or Alzheimer, 26 so could VD be considered a biomarker for microvascular abnormalities after the infection of SARS-CoV-2? Longitudinal studies over time will be necessary to assess vascular outcomes in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…If this is just a local finding or similar changes could be found in other organs remains an unsolved question. Other studies have suggested VD in central retina as a possible vascular biomarker and examined its relationship with systemic conditions: diabetes, 23 chronic kidney disease, 24 inflammatory bowel disease, 25 amyloidosis 26 or Alzheimer, 26 so could VD be considered a biomarker for microvascular abnormalities after the infection of SARS-CoV-2? Longitudinal studies over time will be necessary to assess vascular outcomes in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The retina and brain share similar microvascular anatomy, and while direct visualisation of CBF is difficult, retinal imaging is comparatively convenient [14]. Retinal structural and blood flow changes associated with systemic and central nervous system illness are increasingly reported [15][16][17] with the use of ocular imaging to assess systemic disease termed "oculomics" [18]. Retinal changes may, therefore, associate with CBF in critically ill patients, offering a novel biomarker to monitor in realtime and reduce cerebral hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…There was no association between a diagnosis of Crohn’s disease or ulcerative colitis and retinal blood flow, but when either group of patients had active disease, FAZ area was reduced compared to patients in remission, suggesting altered retinal blood flow autoregulation by systemic inflammatory status [ 16 ]. Systemic sclerosis has involvement of the microvasculature as one of the earliest features.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations